PENGARUH MOTIVASI, KEPUASAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA DOSEN PADA POLITEKNIK SWASTA KOTA PALEMBANG - Cahyani Eni (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
This study aims to determine the effect of motivation, job satisfaction and leadership style,on the performance of Private Polytechnic lecturer in Palembang City. The population thatbecome the object of research are lecturer of Polytechnic of Anika, Polytechnic of Palcomtech,Polytechnic of Akamigas and Polytechnic of Darussalam with status of permanent lecturer,sampling technique is census (sample saturation) 96 people, processed data 72 primary data.This research was analyzed using data analysis with Structural Equation Modeling. Partially,motivation variable have positive effect on lecturer performance but not significant while jobsatisfaction have positive and significant influence to service quality whileleadership style has no effect to lecturer performance.Keywords: Motivation, Job Satisfaction, Leadership, Performance and Polytechnic